Quantum Simulation of Quantum Field Theory in the Front Form - Kreshchuk, Michael. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Physics.; Advisor: Peter Love.; Committee: Gary Goldstein, Timothy Atherton, Cristian Staii, and Stanley Brodsky.; Keywords: Quantum physics, Physics, and Computational physics.